Transformative Islamic Education: Insights from Ma'had al-Jami'ah Raden Intan Lampung - Erlina, Erlina; Zulhannan, Zulhannan; Hijriyah, Umi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study explores the implementation of transformative Islamic education at Ma'had al-Jami'ah Raden Intan Lampung, with a focus on its management practices and organizational culture. Using a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that Ma'had al-Jami'ah implements a participatory and inclusive management system, guided by values of integrity, collaboration, and hard work. This approach fosters a holistic educational environment that integrates Islamic principles with modern management strategies, aligning spiritual growth with intellectual development. The study underscores the significance of transformative Islamic education in addressing contemporary challenges by bridging religious and modern scientific knowledge. While the findings provide valuable insights into the management of Islamic education, the study's scope is limited to a single institution, necessitating further research across diverse settings. This research contributes to the theoretical understanding of Islamic education management and offers practical recommendations for adopting transformative educational practices in similar contexts.